Anti-individualism and knowledge - Brown, Jessica (Jessica Anne) (Contemporary philosophical monographs ;, 2004)
Contemporary philosophy of mind is dominated by anti-individualism, which holds that a subject's thoughts are determined not only by what is inside her head but also by aspects of her environment. Despite its dominance, anti-individualism is subject to a daunting array of epistemological objections: that it is incompatible with the privileged access each subject has to her thoughts, that it undermines rationality, and, absurdly, that it provides a new route to a priori knowledge of the world. In this rigorous and persuasive study, Jessica Brown defends anti-individualism from these epistemological objections. The discussion has important consequences for key epistemological issues such as skepticism, closure, transmission, and the nature of knowledge and warrant. According to Brown's analysis, one main reason for thinking that anti-individualism is incompatible with privileged access is that it undermines a subject's introspective ability to distinguish types of thoughts. So diagnosed, the standard focus on a subject's reliability about her thoughts provides no adequate reply. Brown defuses the objection by appeal to the epistemological notion of a relevant alternative. Further, she argues that, given a proper understanding of rationality, anti-individualism is compatible with the notion that we are rational subjects. However, the discussion of rationality provides a new argument that anti-individualism is in tension with Fregean sense. Finally, Brown shows that anti-individualism does not create a new route to a priori knowledge of the world. While rejecting solutions that restrict the transmission of warrant, she argues that anti-individualists should deny that we have the type of knowledge that would be required to use a priori knowledge of thought content to gain a priori knowledge of the world.